The Effect of Service Quality, Brand Image, And Price Perception on Word of Mouth In Wedding Organizer Services at PT. Euforia Unggul Berkarya - M. Lucky Pratama; Diah Natalisa; Aslamia Rosa (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study aims to analyze the influence of service quality, brand image, and price perception on electronic word of mouth (e-WOM) for wedding organizer services at PT. Euforia Unggul Berkarya. The study involved all 100 respondents from the company's clients, ensuring the data obtained comprehensively represents consumer perceptions. Data collection involved primary and secondary data, with a questionnaire as the primary instrument to measure respondents' perceptions of the research variables. The data were then analyzed using multiple linear regression analysis to determine the effect of each independent variable on e-WOM. The results show that service quality has a significant influence on e-WOM, indicating that responsive, professional, and service that meets customer expectations encourages clients to share their positive experiences through digital media. Furthermore, brand image also significantly influences e-WOM, indicating that reputation, credibility, and positive perceptions of the company play a significant role in shaping consumers' willingness to recommend the service to others. These findings suggest that a strong brand image can increase customer trust and loyalty, which is then reflected in e-WOM activity. Furthermore, price perception also has a significant influence on e-WOM. This indicates that prices that are perceived as reasonable and commensurate with the quality of service received will increase consumer satisfaction, thereby encouraging the emergence of positive reviews and recommendations. Overall, the results of this study confirm that the synergy between service quality, brand image, and price perception is a crucial factor in increasing e-WOM in wedding organizer services, particularly at PT. Euforia Unggul Berkarya